Notas acerca de la extensión, intensidad y cronología del vascuence peninsular antiguo (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The article is devoted to some thoughts on the spread, strength and chronology of the Peninsular ancient Basque language. In relation to a recent work which points out the Vasconization of present day Euskadi and Navarre as having occurred between the 6th and the 11th century, it is given a chronology based on sure proofs which goes back to the 1st century BC. Additionally, Indo-European etymologies are offered for the theonym Stelaitse (dat.) and Iviliae (dat.). From the analysis of a geographically marginal terri- tory, that of the Las Encartaciones in Biscaye, a series of place names in – (e/a)ran is detected and this phenomenon is hypothetically put in relation with the first Basque language speakers there in Early Medieval Times. The work ends by thinking about the Peninsular ancient Basque language in a more wide context and warning on the lack of testimonies in the territories of Caristians and Vardullians.
Keywords: Ancient Basque Language; Indo-Europena Etymologies; Vasconization; Early Medieval Period